1996
DOI: 10.1007/bf00195724
|View full text |Cite
|
Sign up to set email alerts
|

Changes in blue-light-dependent protein phosphorylation during the early development of etiolated oat seedlings

Abstract: Blue light induced the phosphorylation of a 116-kDa plasma-membrane-associated protein in dark-grown seedlings from Avena sativa L. The response was restricted to the phototropically sensitive tissue of the coleoptile tip. Surprisingly, this protein showed different properties in membrane preparations from plants that were grown for 3 d than in those from 5-d-old seedlings. In contrast to the younger coleoptiles, in 5-d-old seedlings phosphorylation of the 116-kDa protein depended strictly on the addition of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 12 publications
2
15
0
Order By: Relevance
“…These times were similar to the half-lives of activated A. diantum capillus-veneris phot2-LOV1ϩLOV2 obtained by spectroscopy. Furthermore, it was shown that At phot1 retained autophosphorylation activity in the dark after the cessation of a light pulse (4,39) and that its time course was similar to the dark regeneration of D450 of At phot1 (13). The dark regeneration in At phot1 was also shown to correlate with the recovery of phototropic sensitivity following a saturating pulse of light (40).…”
Section: P2l2k As a Bl-regulated Kinase With Dark Activity-p1l2kmentioning
confidence: 83%
“…These times were similar to the half-lives of activated A. diantum capillus-veneris phot2-LOV1ϩLOV2 obtained by spectroscopy. Furthermore, it was shown that At phot1 retained autophosphorylation activity in the dark after the cessation of a light pulse (4,39) and that its time course was similar to the dark regeneration of D450 of At phot1 (13). The dark regeneration in At phot1 was also shown to correlate with the recovery of phototropic sensitivity following a saturating pulse of light (40).…”
Section: P2l2k As a Bl-regulated Kinase With Dark Activity-p1l2kmentioning
confidence: 83%
“…Changes in redox state are also known to activate ion channels in Arabidopsis leaves and could be an important aspect of the mechanism by which BL activates anion channels. Anionchannel activity could also be influenced through phos-phorylation events (Schmidt et al, 1995;Pei e t al., 1997), which are known to be important in the early stages of the BL signal transduction pathway leading t o phototropism (Short a n d Briggs, 1994; Liscum a n d Briggs, 1995;Salomon et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…In etiolated seedlings, both cosedimentation with known plasma membrane marker enzymes (Gallagher et al, 1988;Hager and Brich, 1993) and aqueous two-phase partitioning (Palmer et al, 1993;Short et al, 1993;Salomon et al, 1996;Sharma et al, 1997) conclusively locate unphosphorylated phot1 to the plasma membrane. Because phot1 is highly hydrophilic and has no obvious membrane-spanning domains, it is clearly not an integral membrane protein.…”
Section: Introductionmentioning
confidence: 99%